2020
DOI: 10.1186/s13643-020-1270-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension among patients with comorbidities in sub-Saharan Africa: protocol for a systematic review and meta-analysis

Abstract: Background: Uncontrolled hypertension is the most important risk factor and leading cause of cardiovascular diseases. It is predicted that the number of people with hypertension will increase, and a large proportion of this increase will occur in developing countries. The highest prevalence of uncontrolled hypertension is reported in sub-Saharan Africa, and treatment for hypertension is unacceptably low. Hypertension commonly co-exists with comorbidities and this is associated with poorer health outcomes for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Hypertension is responsible for at least 45% and 51% of deaths due to heart disease, and stroke, respectively [ 5 ]. The health system in SSA has the worst performance, with only 18–29.9% of participants received treatment, and 5–10.3% achieved control of their hypertension [ 6 , 7 ]. In reality, it could be possible to achieve adequate blood pressure (BP) targets in about 70–80% of patients by improving adherence and/or intensifying drug therapy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is responsible for at least 45% and 51% of deaths due to heart disease, and stroke, respectively [ 5 ]. The health system in SSA has the worst performance, with only 18–29.9% of participants received treatment, and 5–10.3% achieved control of their hypertension [ 6 , 7 ]. In reality, it could be possible to achieve adequate blood pressure (BP) targets in about 70–80% of patients by improving adherence and/or intensifying drug therapy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…20,28,29 In sub-Saharan Africa, hypertension is still underdiagnosed or poorly controlled among those who are on treatments which further contribute to poor treatment outcomes in stroke patients. 30 This trend might be due to low awareness, limited access to healthcare, and a lack of a healthy lifestyle. Preventing, timely diagnosing, and treating hypertension as well as promoting public awareness can help to decrease the burden of cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled hypertension (UHTN) in SSA is a challenge despite increasing knowledge of hypertension care and the availability of low-cost medications. [5] A 2013 systematic review showed a very low level of treatment (18%) and a high (97%) prevalence of uncontrolled hypertension in SSA [6] . Morbidities, such as stroke, associated with uncontrolled hypertension are costly to treat and pose a burden to health care systems in SSA that are already weak.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidities, such as stroke, associated with uncontrolled hypertension are costly to treat and pose a burden to health care systems in SSA that are already weak. High uncontrolled rates of hypertension have economic and public health implications [6] . Among patients who have detected HTN, few are taking treatment and, among those on treatment, very few are controlled [7] .…”
Section: Introductionmentioning
confidence: 99%